Necessidades formativas dos diretores de escola iniciantes na rede municipal de ensino de São Paulo - Silva, Cristiane Ferreira da (2018)
The present work aimed as a general goal to know the vocational needs and challenges faced in school management by begginer school principals from the school's network of São Paulo and, as specific goals: to characterize begginer school principals, investigate their vocational needs, investigate the main challenges they have to face regarding school managing and to propose some possible vocational actions to be taken on principals' formation. Some correlate studies which approached a principal's vocational needs, a principal's ongoing formation and that dealt with the begginer's principal theme were selected. Theoretical foundation is based upon school managent concepts by Libâneo (2013); continuous and ongoing formation and professional development by Marcelo (2010); vocational needs from Lima (2015), Di Giorgi et al (2011) and Príncepe (2010). It has been also performed an analysis of legislation regarding the subject and documents from City Offie of Education of São Paulo. The survey participants were three school principals belonging to a Regional Management of Education who had until three years of experience on the job. Data has been collected by semi-structured interviews and analysed under prose analysis as proposed by André (1983). Results have shown that: principals have decided to work in that position due to difficulties faced when they were teachers; challenges by them refer to bureaucratic issues, legislation, conflict management, interpersonal relationships, routine and work organization and those issues related to politics and public educational policies. To deal with challenges the principals look for help from the school's management team, from older workmates, from supervisors and from DRE. The needs shown by the principals refer to practical action of everyday actions and the school's functioning